Effects of Joule heating on magnetic field inside a channel along with a cavity - Azad, A. K.; Rahman, M. M.; Öztop, Hakan Fehmi (Elsevier Science Bv, 2014)
A computational solution has been made to obtain flow and temperature field inside a channel with a cavity under magnetic field and joule effect. The left side of the cavity is shorter than right side. Mixed convection heat transfer is studied. Finite element method is used to solve governing equations of laminar flow. The study investigates the effects of three parameters such as Hartmann number, joule parameter and Prandtl numbers for pure mixed convection (Ri = 1). For the specified conditions streamline contours and isotherm contours are obtained and later on the variation of overall Nusselt number and exit temperature are obtained for the aforementioned parameters. It is found that the aforesaid parameters are extremely effective parameter on flow field and temperature distribution. It is also found that both Hartmann number and joule parameter play important role to control the mode of heat transfer. (C) 2014 The Authors. Published by Elsevier Ltd.
10th International Conference on Mechanical Engineering (ICME) -- DEC 20-22, 2013 -- BUET, Dhaka, BANGLADESH
Keywords: Finite element method; open cavity; magnetic field; numerical solution